BIM-Enabled Structural Design: Impacts and Future Developments in Structural Modelling, Analysis and Optimisation Processes - Chi, Hung-Lin; Wang, Xiangyu; Jiao, Y. (Kluwer Academic Publishers, 2014)
This review focuses on identifying the impacts and future development trends for current structural design practice in integration of building information modelling (BIM) technologies. BIM technologies, as novel information management schemes they are, are changing the conventional structure design processes. Currently, utilising BIM technologies for reshaping structural design has been widely acknowledged and embraced by both academic and industry circles. In this research, the current status and issues of the structural design processes (including modelling, analysis, and optimisation of structures) are fully investigated with emphases on specific design stages. The research put efforts on surveying the benefits of BIM in facilitating current structural design, such as systematic modelling processes, powerful interactive visualization platform, and standardised exchanging data interfaces. Impacts of personnel involvement in structural design when adopting BIM have also been identified in detail. Finally, a predicted cross-functional flowchart of BIM-enabled structural design for the near future is proposed, which shows future developing trends in improving structural design quality and addressing current issues.